Shaking table test and numerical simulation of eddy-current tuned mass damper for structural seismic control considering soil-structure interaction. (1st June 2020) - Liu, Shutong; Lu, Zheng; Li, Peizhen; Ding, Sunwei; Wan, Fei
Highlights: Shaking table tests of a six-story steel frame model equipped with ECTMD in SSI system are conducted. The vibration control performance of ECTMD considering SSI effects are studied. Eddy current damping effect in SSI system is evaluated. A finite element model on the shaking table tests is established and verified. The equivalent linear method and bounding surface plasticity model are used respectively for nonlinear behavior of soil. Abstract: This paper firstly investigates the vibration control performance of eddy current tuned mass damper (ECTMD) on structure considering soil-structure interaction (SSI) subjected to seismic loads, and shaking table tests of a six-story steel frame model equipped with ECTMD in SSI system are conducted. By comparison with the undamped TMD, the effectiveness of eddy current damping is also studied. The experimental results in the seismic cases clearly reveal that ECTMD mitigates the maximum displacement response both in rigid base and SSI situations, but it may amplify the peak floor acceleration considering SSI effects. On the whole, SSI decreases the mitigation effects of ECTMD on the structural maximum response, and eddy current damping can improve TMD's control performance, especially in SSI system. Furthermore, a three-dimensional finite element model on the shaking table tests is established. The numerical model utilizes two different analysis procedures - equivalent linear method and bounding surface plasticity model, to simulate the nonlinear behavior of soil, and the concept of an equivalent eddy current damping is used to simulate ECTMD. A comparison of experimental and simulated results shows that the proposed model can accurately estimate the dynamic response of structure equipped with ECTMD in SSI system under earthquake excitations.